Measurement of Company Performance Based on Innovation (Study on Restaurant and Cafe in Padang City) - Asnimar Asnimar; Ratni Prima Lita; M. Ma'ruf (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2022)
This study aims to analyze the role of product innovation, process innovation and organizational innovation on company performance in restaurant and cafe businesses in Padang City. This explanatory research uses surveys, explanatory surveys with a quantitative approach. Data collection on 136 restaurant and cafe business actors in the city of Padang was carried out using the purposive sampling technique. The data were then analyzed using Structural Equation Modeling - Partial Least Square (SEM-PLS). The results show that product innovation has a significant effect on company performance, process innovation has a significant effect on product innovation, process innovation has no significant effect on company performance, organizational innovation has a significant effect on process innovation, and organizational innovation has a significant effect on company performance. This study has several important findings for restaurants and cafes in the city of Padang, to pay more attention to the innovations carried out in their business, especially process innovation and organizational innovation, because process innovation significantly affects product innovation of restaurant and cafe business actors in the city of Padang. Furthermore, organizational innovation significantly affects process innovation, and the performance of restaurant and cafe business actors in the city of Padang.